What's left of Marxism historiography and the possibilities of thinking with Marxian themes and concepts - Zachariah, Benjamin 1972-; Raphael, Lutz 1955-; Bernet, Brigitta 1973- (De Gruyter Oldenbourg, 2020)
Have Marxian ideas been relevant or influential in the writing and interpretation of history? What are the Marxist legacies that are now re-emerging in present-day histories? This volume is an attempt at relearning what the "discipline" of history once knew – whether one considered oneself a Marxist, a non-Marxist or an anti-Marxist
"The volume that is now before you has its origins, as alluded to above, in a workshop, organised by the (DFG-Leibniz) Research Group on "The contemporary history of historiography" situated at Trier University, on the occasion of an international conference on Marxism at this University in the bicentenary year of Karl Marx's birth in May 2018." - Vorwort
Keywords: Class society; Gesellschaftslehre; Karl Marx; Klassengesellschaft; Marxism; Marxismus; Social studies; HISTORY / General; Geschichtsschreibung; Konferenzschrift -- 2018 -- Trier